The Effect of Variations in Cross-Section Reduction Percentage during the Wire Drawing Process on the Tensile Strength and Microstructure of Copper Wire - Bayu Christiawan Raharjo; Margono Sugeng (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Wire drawing is a plastic deformation process used to reduce the diameter of wire by pulling it through a die. The percentage of cross-sectional reduction applied during the process significantly affects the mechanical properties and microstructure of the material. This study aimed to analyze the effect of cross-sectional reduction percentage on the tensile strength and microstructure of copper wire produced by the wire drawing process, as well as to determine the relationship between microstructural changes and tensile strength. Copper wire with an initial diameter of 2.65 mm was used as the test material and processed using three reduction levels of 10%, 20%, and 30%. Tensile testing was carried out using a Universal Testing Machine (UTM), while microstructural observations were performed using an optical microscope at 100× magnification. The results showed that increasing the reduction percentage increased the average Ultimate Tensile Strength (UTS), from 274.01 MPa at 10% reduction to 307.28 MPa at 20%, and 345.26 MPa at 30%. Conversely, the average elongation decreased from 15.50% to 9.60% and 3.50%, respectively. Microstructural observations revealed that higher reduction percentages caused the copper grains to become increasingly elongated, forming a fiber-like structure aligned with the drawing direction due to greater plastic deformation. These microstructural changes increased the dislocation density, resulting in a strain hardening mechanism that improved tensile strength but reduced ductility. Therefore, the variation in cross-sectional reduction had a significant effect on both the mechanical properties and the microstructure of copper wire produced by the wire drawing process.